Triclosan degradation by electro-Fenton process using electrolytic unit with titanium electrodes coated with mixed IrO2/RuO2 - Pérko, Jan; Hansen, Hans Christian Bruun; Weidlich, Tomáš (My University, 2017)
The paper focus on the degradation of a widely used antibacterial agent triclosan (5-chloro-2-(2,4-dichlorophenoxy)phenol) by electro-Fenton process. The electrochemical process was conducted in recirculating setup by passing the reaction mixture through an electrolytic unit consisting of titanium electrodes coated with mixed iridium and ruthenium oxides. An initial triclosan concentration of 10 mg/L was used throughout. Different reaction conditions and their impact on triclosan degradation were studied such as different concentrations of added iron(II) as Fenton reagent, different concentrations of sodium sulfate electrolyte, different flow rates, current density values and different pH values. High triclosan sorption to plastic surfaces of the equipment (tubing, cells etc) was observed and this phenomenon was quantified and taken into account during calculations. About 30 – 50% of triclosan was degraded after 80 minutes of electrolytic process. The optimum conditions for electro-Fenton degradation of triclosan were: current density 24 mA/cm2, flow rate 50 ml/min, pH 4, initial concentration of iron(II) at 5 mg/l, and 2 mmol/l sodium sulfate.
Degradace Triclosanu s použitím elektro-Fentonovy oxidace s použitím titanových elektrod potažených oxidy iridia a ruthenia
Keywords: Degradation; electro-Fenton method; triclosan; advanced oxidation process; degradace; elektro-Fentonova oxidace; triclosan; pokročilé oxidační procesy